Visibility estimation of information objects of the road situation - Горохов, Г.Т.; Чаруха, Ю.Е. (Proceedings of National Aviation University, 2010)
We offer the methodical approach for estimation of visibility of road information objects based on applying the information visibility factor, which special feature is the ability to separate from general information flow only that part which is perceived by human under the specific conditions. Mathematical models of estimation of visibility are based on the theoretical points of works in engineering psychology. There is substantiated transition from informational indicators of pictures to time indicators of visual perception of separate elements of pictures, as well as applying exponential dependence for calculation of the information visibility criteria. Estimation of visibility perception based on the information visibility factor makes it possible to get the indicators, for various observer categories, of the volume of information, expedient for placing on road boards and signs, taking into consideration the location of the road objects.